Binary and Ternary Complexes of Neodymium(III) with Crotonic Acid and Acrylic Acid - Lavale, A.K.; Lavale, S.C. (Asian Journal of Chemistry, 2010)
Polarography between Nd(III) and crotonic acid (CA) + acrylic acid (AA) at pH 2.50 ± 0.02 and 25 ± 1ºC has been used to study complexes. The methods of DeFord and Hume and of Schapp and McMaster have been successfully applied to determine the formation constants of binary and ternary complexes. [Nd(CA)(AA)]+ and [Nd(CA)2(AA)] mixed complexes with formation constants values of log β11 = 6.02 and log β21= 8.58, respectively have been found. Possible mechanisms of electron transfer and complex formation have been described in aqueous media.